The problem of state support of innovation ecosystems - Mykhailo Zuiev (Менеджмент та підприємництво: тренди розвитку, 2025)
This work is intended to be a theoretical generalization of key issues commonly faced by state support of innovative environments in Ukraine. To achieve this aim, it was necessary to solve theoretical scientific problems directed at minimizing the negative impact caused by the lack of state support for innovative environments. In the course of the research, the method of analysis, synthesis and systematization within the systemic approach were used. The framework of research was based on the legal regulation of the innovation system, academic and methodological works of domestic and foreign authors. Also, the study incorporated quantitative or analytical data obtained from government documents and magazines.